Interaction and dynamic changes of microbial communities and volatile flavor compounds during the fermentation process of coffee flower rice wine - Liu, Kunyi; Su, Rui; Wang, Qi; Shen, Xiaojing; Jiang, Bin; Yang, Liran; Li, Zelin; Zheng, Jia; Li, Pingping (Frontiers in Microbiology, 2024)
To develop a unique flavor of rice wine, coffee flowers (by-products of the coffee industry) were added because of its biologically active compounds that are conductive to health, and the fermentation parameters were optimized. Additionally, the dynamic changes of microbial communities and volatile flavor compounds (VFCs) in different fermentation stages were investigated. After fermentation parameters optimization, a novel product, i.e., the coffee flower rice wine (CFRW) was obtained with bright yellow transparent, fragrant and harmonious aroma, mellow and refreshing taste by the sensory evaluation when 4.62% coffee flowers and 1.93% koji were added, respectively, and fermented at 24.10 °C for 3.88 days. The results showed that Lactococcus was the dominant bacteria, accounting for 87.0%-95.7%, while Rhizopus and Cladosporium were the main fungi, accounting for 68.2% and 11.3% on average, respectively, in the fermentation process of CFRW. Meanwhile, 23 VFCs were detected in CFRW, including 3 alcohols, 6 terpenes, 10 esters, 3 aromatics and 1 furan. Correlation analysis revealed that there were 16 significant positive correlations and 23 significant negative correlations between bacterium and VFCs (|ρ| > 0.6, P < 0.05), respectively; while, there were 12 significant positive correlations and 1 significant negative correlation between fungi and VFCs (|ρ| > 0.6, P < 0.05). Furthermore, five VFCs, including linalool, geraniol, ethyl acetate, 1-hexanol and 3-methyl-1-butanol, contributed vital flavors to CFRW and they were all significant negatively correlated with the changes of Massilia and Acinetobacter (|ρ| > 0.6, P < 0.05); a significant positive correlation was found between the relative abundance of Lactococcus and the contents of 3-methyl-1-butanol and ethyl acetate (|ρ| > 0.6, P < 0.05). Thus, this study will provide a valuable theoretical basis for further improving the quality and production technology of CFRW.